Analisis Flypaper Effect dan Pengaruhnya Terhadap Pertumbuhan Ekonomi Melalui Mediasi Belanja Daerah - Achmad Rizqullah; Meldona Meldona (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The regional government allocates funds in the form of regional budgets in the APBD to increase fixed assets. So far, regional spending has been used more for routine spending which is relatively less productive. The purpose of this study is to analyze the effect of Regional Original Income (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH) on regional Expenditure Allocation in Bima City government. The population of this study is the financial report of the Bima City APBD realization for 17 years starting from 2004 to 2021, while the research sample uses 5 years, which is from 2017 to 2021. The secondary data used in this research is the Bima City Government APBD Realization Report. Hypothesis testing in this study used Smart PLS. Research shows that PAD and DAU have a significant effect on economic growth. However, PAD and DAU have no effect on Regional Spending, and Regional Expenditure cannot mediate the influence of PAD and DAU on economic growth. The results showed that there was no flypaper effect phenomenon in the Bima City Government Budget.